Perspectives on European Educational Policy and Practice (PEEPP) : papers from the Erasmus Intensive Programme Summer School, Haapsalu, 2009 and 2010 - Garland, Paul [Herausgeber] (My University, 2012)
This volume collects 15 papers, which are the result of an Erasmus-funded Intensive Programme for doctroral and masters students named "Perspectives on European Educational Policy and Practice (PEEPP)". This programme aims to enable students to share research practice and to reflect critically on a range of theoretical and philosophical perspectives informing their established or intended research methodologies in the field of European educational policy and practice. Some of the papers in this volume "take the form of exploratory position papers with an emphasis on key concepts and the literature informing a field of study. Other papers reveal students at the point of theorising the domain of their research interest; and still others report empirical research in process. As an assemblage of early stage research writing, these papers reveal much that is of interest to the comparative researcher on the subject of research methodology." (Hrsg., BIBB-Doku)
Keywords: Bildungsforschung; Berufsbildungsforschung; Europa